2020
DOI: 10.31703/gssr.2020(v-i).24
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Competency Reading and Thinking Skills in Grade VIII English Textbook

Abstract: This research aimed at analysing the Grade VIII English textbook of Punjab Textbook Board against one of the five competencies, the Reading and Thinking skills and identifying the satisfaction level of Grade 8 students with their textbook for the fulfilment of this competency. The main parameters of the content analysis were Competency (C), Standards (S), Benchmarks (B) and SLOs. The data was collected through content analysis (of the textbook) and survey questionnaire. The student satisfaction level was measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Reading competency is also well known as the students' ability for comprehending the meaning and the rhetorical steps in the written text, by which it covers with finding out the main idea, specific information, word meaning and textual reference (Baig et al, 2020;Khairuddiniyah, 2018). Someone is capable in achieving the reading competency, if they are able to master four reading indicators, namely: main idea, specific information, word meaning and textual reference (Gheytasi et al, 2015;Khofifah & Ramadan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Reading competency is also well known as the students' ability for comprehending the meaning and the rhetorical steps in the written text, by which it covers with finding out the main idea, specific information, word meaning and textual reference (Baig et al, 2020;Khairuddiniyah, 2018). Someone is capable in achieving the reading competency, if they are able to master four reading indicators, namely: main idea, specific information, word meaning and textual reference (Gheytasi et al, 2015;Khofifah & Ramadan, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The findings revealed that the syllabus focused only on developing the writing skills and did not demonstrate different techniques for handling compositions. Baig et al (2020) conducted a research on the same textbook understudy. The framework of the research was the reading and thinking skills competency of the Pakistani English Curriculum (Government of Pakistan, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Baig et al (2020) conducted a research on the same textbook understudy. The framework of the research was the reading and thinking skills competency of the Pakistani English Curriculum (Government of Pakistan, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are several previous studies that analysed reading activities in English textbooks. One of the researchers analyse the Grade VIII English textbook of Punjab Textbook Board against one of the five competencies, the Reading and Thinking skills and identifying the satisfaction level of Grade 8 students with their textbook for the fulfilment of this competency (Baig et al, 2020). The results of content analysis and students' survey showed that the textbook partly meets the requirements related to the selected competency.…”
Section: Introductionmentioning
confidence: 99%